Allied Chemistry DE 17UMA4A73-1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 10

Diffrential Equation

Course code :17UMA4A7:3 (chemistry)


1) The order of the differential equation (𝑦 ′′ )2 + 𝑦 = 𝑒 𝑥 is

a) 0 b) 1 c) 2 d) None of these
3⁄
2) The degree of the differential equation (𝑦 ′ ) 2 = 𝑦 ′′ is?

a) 0 b) 1 c) 2 d) None of these

3) The integral curves of the differential equation 𝑦 ′ = 1 are?

a) 𝑦 = 𝑥 + 𝑐 b) 𝑦 = 𝑥 2 + 𝑐 c) 𝑦 = 𝑥 3 + 𝑐 d) 𝑦 = 𝑥 + 1

4) Which of the following is a linear differential equation?

a) 𝑦 ′′ + (𝑦 ′ )2 = sin 𝑥 b) (𝑦 ′′ )2 + 3𝑦 = 𝑒 𝑥 c) 𝑦 ′′ + 3𝑦 ′ + 𝑦 = 0 d) (𝑦 ′′ )2 + (𝑦 ′ )3 + 𝑒 𝑥 = 0

5) Which of the following is a separable differential equation?


𝑑𝑦 𝑥2 𝑑𝑦 𝑥+𝑦 𝑑𝑦 𝑑𝑦
a) 𝑑𝑥 = 1−𝑦 2 b) 𝑑𝑥 = 𝑥−𝑦 c) 𝑑𝑥 + (sin 𝑥)𝑦 = 𝑒 𝑥 d) (𝑑𝑥 )2 + (sin 𝑥)𝑦 = 0

6) An integrating factor of the differential 𝑡𝑦 ′ + 2𝑦 = 4𝑡 2 is?

a)𝑡 3 b) 𝑡 4 c) 𝑡 2 d) None of these


𝑑𝑦 𝑦
7) A homogenous differential equation 𝑑𝑥 = 𝑓( ⁄𝑥 ) can be converted to a variable separable

Equation using a transformation:

a)𝑦 = 𝑣𝑥 b) 𝑦 2 = 𝑣𝑥 c) 𝑦 = 𝑣𝑥 2 d) 𝑦 = 𝑣 2 𝑥

8) The differential equation (6𝑥𝑦 2 + 4𝑥 3 𝑦)𝑑𝑥 + (6𝑥 2 𝑦 + 𝑥 4 + 𝑒 𝑦 )𝑑𝑦 = 0 is?

a) a separable equation b) a linear equation c) an exact equation d) a homogenous

linear equation

9) An integrating factor of the differential equation 3(𝑥 2 + 𝑦 2 )𝑑𝑥 + 𝑥(𝑥 2 + 3𝑦 2 + 6𝑦)𝑑𝑦 = 0 is

a) 𝑒 −𝑦 b) 𝑒 2𝑦 c) 𝑒 𝑦 d) 𝑒 −2𝑦

10) The solution of the differential equation 𝑦 ′ = 𝑦 2 , 𝑦(0) = 1 exists in the region

a) (0, ∞) b) (−∞, 0) c) (−∞, 1) d) (−∞, ∞)

11) An integrating factor of the differential equation 𝑦(2𝑥 − 𝑦 + 2)𝑑𝑥 + 2(𝑥 − 𝑦)𝑑𝑦 = 0 is

a) 𝑒 𝑥 b) 𝑒 −𝑥 c) 𝑒 2𝑥 d) 𝑒 −2𝑥
12) The general form of a first or linear equation is
𝑑𝑦 𝑑2𝑦
a) 𝑑𝑥 + 𝑃𝑦 = 𝑄 Where P and Q are functions of x b) 𝑑𝑥 2 + 𝑃𝑦 = 𝑄 where P is a function of x
𝑑𝑦
c) 𝑑𝑥 = 𝑄 Where Q is a functions of x d) None of these

13) The general solution of the differential equation 𝑦 ′ = cos 𝑥 is

a) 𝑦 = sin 𝑥 b) 𝑦 = cos 𝑥 c) 𝑦 = 𝑐 sin 𝑥 d) 𝑦 = sin( 𝑥) + 𝑐

14) The general solution of the differential equation 𝑦 ′′ + 𝑦 = 0 is

a) 𝑦 = 𝑎 sin 𝑥 + 𝑏 cos 𝑥 b) 𝑦 = 𝑎 sin 𝑥 c) 𝑦 = 𝑏 cos 𝑥 d) 𝑦 = sin 𝑥 − cos 𝑥

15) The differential equation 𝑀𝑑𝑥 + 𝑁𝑑𝑦 = 0 is exact if


𝜕𝑀 𝜕𝑁 𝜕𝑀 𝜕𝑁 𝜕𝑀
a) 𝑀 = 𝑁 b) = c) = d) =0
𝜕𝑦 𝜕𝑥 𝜕𝑥 𝜕𝑦 𝜕𝑦

1 𝜕𝑀 𝜕𝑁
16) If 𝑁 ( 𝜕𝑦 − 𝜕𝑥 ) is a function of x only, then an integrating factor of 𝑀𝑑𝑥 + 𝑁𝑑𝑦 = 0 is

1 𝜕𝑀 𝜕𝑁 1 𝜕𝑀 𝜕𝑁
a) 𝜇(𝑥) = exp⁡[∫ 𝑁 ( 𝜕𝑦 − 𝜕𝑥 )𝑑𝑥] b) 𝜇(𝑥) = exp⁡[∫ 𝑁 ( 𝜕𝑦 + 𝜕𝑥 )𝑑𝑥]

1 𝜕𝑀 𝜕𝑁 1 𝜕𝑀 𝜕𝑁
c) 𝜇(𝑥) = ∫ ( − )𝑑𝑥 d) 𝜇(𝑥) = ∫ ( − )𝑑𝑥
𝑁 𝜕𝑦 𝜕𝑥 𝑁 𝜕𝑥 𝜕𝑦

1 𝜕𝑁 𝜕𝑀
17) If ( − ) is a function of y only, then an integrating factor of the differential equation
𝑀 𝜕𝑥 𝜕𝑦

𝑀𝑑𝑥 + 𝑁𝑑𝑦 = 0 is
1 𝜕𝑁 𝜕𝑀 1 𝜕𝑁 𝜕𝑀
a) 𝜇(𝑥) = exp⁡[∫ 𝑀 ( 𝜕𝑥 − )𝑑𝑦] b) 𝜇(𝑥) = exp⁡[∫ 𝑀 ( 𝜕𝑥 + 𝜕𝑦 )𝑑𝑦]
𝜕𝑦

1 𝜕𝑁 𝜕𝑀 1 𝜕𝑁 𝜕𝑀
c) 𝜇(𝑥) = ∫ 𝑀 ( 𝜕𝑥 − 𝜕𝑦 )𝑑𝑦 d) 𝜇(𝑥) = ∫ 𝑀 ( 𝜕𝑥 − )𝑑𝑦
𝜕𝑦

𝑑𝑥
18) An integrating factor of the differential equation 𝑑𝑦 + 𝑃(𝑥) = 𝑄(𝑥) is
2 𝑑𝑥
a) 𝑒 ∫ 𝑃𝑑𝑥 b) 𝑒 − ∫ 𝑃𝑑𝑥 c) 𝑒 ∫ 𝑃 d) 𝑒 ∫(𝑃+𝑄)𝑑𝑥
𝑑𝑥
19) An integrating factor of the differential equation 𝑑𝑦 + 𝑃𝑥 = 𝑄 Where P and Q are functions

Of y alone is
2 𝑑𝑦
a) 𝑒 ∫ 𝑃𝑑𝑦 b) 𝑒 − ∫ 𝑃𝑑𝑦 c) 𝑒 ∫ 𝑃𝑑𝑥 d) 𝑒 ∫ 𝑃
𝑑𝑦
20) The general solution of differential equation (𝑥 + 1) 𝑑𝑥 + 1 = 2𝑒 −𝑦
1
a) 𝑒 𝑦 (𝑥 + 1) − 2𝑥 + 𝑦 = 𝑐 b) 𝑒 𝑦 (𝑥 + 1) = 2𝑥 + 𝑐 c) 1+𝑥 − 𝑦 = 𝑐 d) None of these
21) The characteristic equation of the differential equation (𝐷2 − 4𝐷 + 4)𝑦 = 0 is

a) (𝜆 − 2)3 = 0 b) (𝜆 + 2)2 = 0 c) (𝜆 − 2)2 = 0 d) (𝜆 − 1)(𝜆 − 2) = 0

22) The general solution of the differential equation (𝐷2 − 4𝐷 + 4)𝑦 = 0 is

a) (𝑐0 + 𝑐1 𝑥)𝑒 2𝑥 b) (𝑐0 − 𝑐1 𝑥)𝑒 2𝑥 c) 𝑐1 𝑒 𝑥 𝑐2𝑒 −2𝑥 d) 𝑐1 𝑒 2𝑥 + 𝑐2 𝑒 2𝑥

23) The characteristic roots of the differential equation (𝐷2 − 8𝐷 + 25)𝑦 = 4 cos 3 2𝑥 are

a) Real b) Complex c) Real and Complex d) None of these

24) The characteristic roots of the differential equation (𝐷2 − 2𝐷)𝑦 = 4𝑥 2 + 2𝑥 + 3 are

a) 𝜆 = 0, 𝜆 = −2 b) 𝜆 = 1, 𝜆 = 3 c) 𝜆 = 0, 𝜆 = 2 d) 𝜆 = 1, 𝜆 = −2

25) The general solution of the differential equation (𝐷2 + 2𝐷 + 3)𝑦 = 0 is

a) 𝑦 = 𝑒 −𝑥 [𝑐1 cos 2𝑥 + 𝑐2 sin 2𝑥] b) 𝑦 = 𝑒 𝑥 [𝑐1 cos √2𝑥 + 𝑐2 sin √2𝑥]

c) 𝑦 = 𝑒 −𝑥 [𝑐1 cos √2𝑥 + 𝑐2 sin √2𝑥] d) None of these

26) A particular solution of the differential equation 𝑦 ′′ + 4𝑦 = sec 2𝑥 is


1 𝑥 1 𝑥
a) 4 cos 2𝑥 log cos 2𝑥 + 2 sin 2𝑥 b) 4 sin 2𝑥 log cos 2𝑥 + 2 cos 2𝑥

c) cos 2𝑥 + sin 2𝑥 d) log (cos 2𝑥) + log(sin 2𝑥)

27) A particular solution of the differential equation 𝑦 ′′ + 𝑦 = tan 𝑥 is

a) cos 𝑥 log(sec 𝑥 + tan 𝑥) b) cos 𝑥 log(sin 𝑥 + cos 𝑥) c) log(sin 𝑥 + cos 𝑥) d) log sin 𝑥

28) A particular solution of 𝑦 ′′ + 5𝑦 ′ + 6𝑦 = 𝑒 2𝑥 is


𝑒 2𝑥 𝑒𝑥
a) b) 20 c) 𝑒 2𝑥 d) 𝑒 −2𝑥
20

29) The general solution of the differential equation 𝑦 ′′ − 𝑦 ′ − 2𝑦 = 0 is

a) 𝑦 = 𝑐1 𝑒 −2𝑥 + 𝑐2 𝑒 −𝑥 b) 𝑦 = 𝑐1 𝑒 −𝑥 + 𝑐2 𝑒 2𝑥 c) 𝑦 = 𝑐1 𝑒 𝑥 + 𝑐2 𝑒 2𝑥 d) 𝑦 = 𝑒 𝑥

30) The auxiliary equation of the differential equation (𝐷2 − 4𝐷 + 4)𝑦 = 𝑒 2𝑥 is

a) (𝑚 + 2)2 = 0 b) (𝑚 − 2)2 = 0 c) (𝑚 − 1)(𝑚 − 2) = 0 d) 𝑚2 + 1 = 0

31) A particular integral of the differential equation (𝐷2 − 2𝐷 + 1)𝑦 = 𝑒 𝑥 sin 𝑥 is

a) 𝑒 𝑥 sin 𝑥 b) −𝑒 𝑥 sin 𝑥 c) 𝑒 𝑥 cos 𝑥 d) 𝑒 𝑥

32) A particular integral of the differential equation (3𝐷2 + 𝐷 − 14)𝑦 = 13𝑒 2𝑥 is

a) 𝑥𝑒 2𝑥 b) 𝑒 2𝑥 c) 𝑥 3 𝑒 2𝑥 d) 𝑥 3
33) The general solution of the differential equation (𝐷2 − 4𝐷 + 13)𝑦 = 0 is

a) 𝑒 2𝑥 [𝑐1 cos 3𝑥 + 𝑐2 sin 3𝑥] b) 𝑒 2𝑥 [𝑐1 cos 3𝑥 + 𝑐2 𝑒 𝑥 ]

c) 𝑒 2𝑥 [𝑐1 sin 𝑥 + 𝑐2 cos 𝑥] d) 𝑒 2𝑥 [cos 3𝑥 + sin 3𝑥]

34) The roots of the auxiliary equation of the differential equation 𝑦 ′′ − 2𝑦 ′ + 𝑦 = 𝑥 2 𝑒 3𝑥 are

a) 2, 2 b) 1, 1 c) -1, -1 d) 1, 0

35) The general solution of (𝐷2 − 6𝐷 + 9)𝑦 = 0 is

a) (𝑐1 + 𝑐2 𝑥 2 )𝑒 3𝑥 b) (𝑐1 + 𝑐2 𝑥)𝑒 3𝑥 c) (𝑐1 + 𝑥)𝑒 3𝑥 d) 𝑒 3𝑥

36) The general solution of the differential equation 𝑦 ′ + 𝑦 = 0 is

a) 𝑦 = 𝑐1 sin 𝑥 + 𝑐2 cos 𝑥 b) 𝑦 = 𝑐1 sin 2𝑥 + 𝑐2 cos 2𝑥

c) 𝑦 = 𝑐1 sin √2𝑥 + 𝑐2 cos √2𝑥 d) 𝑦 = sin 𝑥 + cos 𝑥

37) The general solution of (𝐷2 + 4𝐷 + 7)𝑦 = 0 is

a) 𝑦 = [𝑐1 cos √3𝑥 + 𝑐2 sin √3𝑥]𝑒 −2𝑥 b) 𝑦 = 𝑐1 cos √2𝑥 + 𝑐2 sin √2𝑥

c) 𝑦 = 𝑐1 cos √5𝑥 + 𝑐2 cos √5𝑥 d) cos √3𝑥 + sin √3𝑥

38) General solution of the second order differential equation 𝑦′′ + 𝑝𝑦 ′ + 𝑞𝑦 = 0,


for ( 𝑝2 − 4𝑞 < 0), is
a) y = 𝑒 𝑎𝑥 (⁡𝑐1 𝑐𝑜𝑠 𝑏𝑥 − ⁡𝑐2 𝑠𝑖𝑛 𝑏𝑥) b) y = 𝑒 𝑎𝑥 (⁡𝑐1 𝑐𝑜𝑠 𝑏𝑥 + ⁡ 𝑐2 𝑠𝑖𝑛 𝑏𝑥)

c) y = 𝑒 −𝑎𝑥 (⁡𝑐1 𝑐𝑜𝑠 𝑏𝑥 − ⁡ 𝑐2 𝑠𝑖𝑛 𝑏𝑥) d) none of these

39) A particular integral of the differential equation (D 2 + D+1) y = x2 is

a) x2 b) x2 - 2x c) 2x d) x2 + 2x

40) A particular integral of the differential equation (D 2 + D+1) y = ex is


𝑒𝑥
a) ex b) 3ex c) 2ex d) 3

41) Eliminate of arbitrary constants from z= ax+by


a) z= x+y b) z=x-y c) z=xy d) z= px+qy
42) Eliminate of arbitrary constants from z= ax+by+a
a) z= x+y b) z= px+qy c) z= px+qy+p d) z= px+qy+q
43) Eliminate of arbitrary function from z= f(x+y)
a) z= x+y b) p-q=0 c) py-qy=0 d) z= px+qy
44) Eliminate of arbitrary function from z= f(x 2+y2)
a) z= x+y b) p-q=0 c) py-qx=0 d) z= px+qy
45) Eliminate a and b from z= (a+x)(b+y)
a) z= pq b) p-q=0 c) py-qx=0 d) z= px+qy
46) Eliminate a from z= a+x
a) z= pq b) p-q=0 c) py-qx=0 d) none of these
47) Eliminate a and b from z= a+ax+b+by
a) z= p+q b) z= px+qy c) z= px+qy+p+q d) z= px+qy+qp
48) A partial differential equation requires

a) exactly one independent variable b) two or more independent variables

c) more than one dependent variable d) dependent and independent variables are equal

49) If z=ax+by+c is a solution of the equation _______

a) f(p,a)=0 b) f(q,b)=0 c) f(p,q)=0 d) f(a,b)=0

50) Complete integral of the first order PDE of the form f(p,q)=0 is
a) z=ax+by+c b) z=ax+bF(y)+c c) z=ax+F(a)y+c d) none of this

51) Complete integral of pq=1 is


1
a) z=ax+by+c b) z=ax+𝑎 ⁡𝑦+c c) z=ax+ay+c d) none of this

52) Complete integral of p+q=1 is


1
a) z=ax+by+c b) z=ax +⁡𝑎 ⁡𝑦+c c) z=ax+a2 y+c d) z = a x+(1-a)y +c

53) Complete integral of the first order PDE of the form f(x, p, q)=0 is
a) z=ax+by+c b) 𝑧 = ∫ 𝜙(𝑥, 𝑎)𝑑𝑥 + 𝑎𝑦 + 𝑏 c) 𝑧 = ∫ ∫ 𝜙(𝑥, 𝑦)𝑑𝑥𝑑𝑦 + 𝑎𝑦 + 𝑏

d) 𝑧 = ∫ 𝜙(𝑦, 𝑎)𝑑𝑦 + 𝑎𝑥 + 𝑏
54) Complete integral of the first order PDE of the form f(x, p, q)=0 is
a) z=ax+by+c b) 𝑧 = ∫ 𝜙(𝑥, 𝑎)𝑑𝑥 + 𝑎𝑦 + 𝑏 c) 𝑧 = ∫ ∫ 𝜙(𝑥, 𝑦)𝑑𝑥𝑑𝑦 + 𝑎𝑦 + 𝑏

d) 𝑧 = ∫ 𝜙(𝑦, 𝑎)𝑑𝑦 + 𝑎𝑥 + 𝑏

55) Complete integral of p+q=x is

𝑥2
a) z=ax+by+c b) z=ay+( 2 − 𝑎𝑥)+c c) z=ax+a2 y+c d) z = a x+(1-a)y +c

56) Complete integral of the first order PDE of the form f(z, p, q)=0 is
𝑑𝑧
a) z=ax+by+c b) 𝑧 = ∫ ∫ 𝜙(𝑥, 𝑦)𝑑𝑥𝑑𝑦 + 𝑎𝑦 + 𝑏 c) ∫ = 𝑥 + 𝑎𝑦 + 𝑏
𝜙(𝑥,𝑎)

d) 𝑧 = ∫ 𝜙(𝑦, 𝑎)𝑑𝑦 + 𝑎𝑥 + 𝑏

57) Complete integral of p=2qx is

a) z=ax+by+c b) z=ay+ax2+c c) z=ax+a2 y+c d) z = a x+(1-a)y +c


58) Complete integral of z=px +qy+ log (pq) is

a) z=ax +by+ log (ab) b) x=ax +by+ log (ab) c) z=ax +by d) z=ax +by+ ab

59) The general solution of x p+yq = z is


−𝑥 2𝑦 𝑥 𝑦
a)⁡𝑓 ( 𝑧 , )=0 b) 𝑓(𝑥, 𝑦) = 0 c) 𝑓(𝑥 2 , 𝑦 2 ) = 0⁡ d) 𝑓 ( 𝑧 , 𝑧 ) = 0
𝑧

60) The general solution of x p+yq = 0 is


−𝑥 2𝑦 𝑥 𝑦
a)⁡𝑓 ( 𝑧 , )=0 b) 𝑓(𝑥𝑦, 𝑧) = 0 c) 𝑓(𝑥 2 , 𝑦 2 ) = 0⁡ d) 𝑓 ( 𝑧 , 𝑧 ) = 0
𝑧

61) The Laplace transform of the unit step function 𝑢(𝑡−𝑎) is


−𝑎𝑠 𝑎𝑠 −𝑎𝑠
a) 𝑒 −𝑎𝑠 b) 𝑒 ⁄𝑠 c) 𝑒 ⁄𝑠 d) 𝑒 ⁄𝑠 2

62) The Laplace transform of 𝑒 𝑎𝑡 is


1 1 1
a) 𝑠−𝑎 b) 𝑠+𝑎 c) 𝑠2 −𝑎2 d) None of these

63) The Laplace transform of cos 𝑎𝑡 is


𝑠 1 1 𝑠
a) b) c) d)
𝑠2 +𝑎2 𝑠2 +𝑎2 𝑠2 −𝑎2 𝑠2 −𝑎2

64) If ℒ{𝑓(𝑡)} = 𝐹(𝑠), then ℒ{𝑒 𝑎𝑡 𝑓(𝑡)} =

a) F(s) b) F(s-a) c) F(s +a) d) F(s/a)

65) If ℒ{𝑓(𝑡)} = 𝐹(𝑠), then ℒ{𝑓(𝑎𝑡)} =


1 𝑠 𝑠 𝑎
a) 𝑎 𝐹(𝑎) b) 𝐹(𝑎) c) 𝐹( 𝑠 ) d) F(s)

66) The Laplace transform of the delta function is

a) 𝑒 −𝑎𝑠 b) 𝑒 𝑎𝑠 c) 𝑒 𝑎𝑠 /𝑠 d) 𝑒 −𝑎𝑠 /𝑠
∞ 𝑒 −𝑡 sin 𝑡
67) ∫0 𝑑𝑡 =
𝑡
𝜋 𝜋 𝜋 −𝜋
a) 2 b) 4 c) 8 d) 2

∞ sin 𝑡
68) ∫0 𝑑𝑡 =
𝑡
𝜋 𝜋 𝜋
a) 4 b) 8 c) 2 d) None of these

69) ℒ{𝑡 𝑛 } =
𝑛! (𝑛+1)! 𝑛! 1
a) 𝑠𝑛 b) 𝑠𝑛
c) 𝑠𝑛+1 d) 𝑠𝑛
4
70) ℒ{sin 4𝑡} = 𝑠2 +16, then ℒ{𝑒 −2𝑡 sin 4𝑡} =
4 1 2
a) 𝑠2 +4𝑠+20 b) 𝑠2 +4𝑠+20 c) 𝑠2 +4𝑠+20 d) None of these
𝑡
71) The Laplace transform of the function 𝑓(𝑡) = {𝑒 ⁡⁡0 < 𝑡 < 1 is
0⁡⁡⁡⁡⁡⁡⁡⁡⁡⁡⁡𝑡 > 1
1 1 1 1
a) (𝑠−1) [1 − 𝑒 (1−𝑠) ] b) (𝑠+1) [1 − 𝑒 (1−𝑠) ] c) 𝑠−1 [1 − 𝑒 𝑠 ] d) 𝑠 [1 − 𝑒 𝑠 ]

72) If 𝑓(𝑡)|𝑡 − 1| + |𝑡 + 1|, then ℒ{𝑓(𝑡)} =


1 −𝑠 1 𝑠 2 −𝑠 2
a) 𝑠 (1 − 𝑒 ⁄𝑠) b) 𝑠2 (1 − 𝑒 ⁄𝑠) c) 𝑠 (1 − 𝑒 ⁄𝑠) d) 𝑠 (1 − 𝑒 −𝑠 )

73) The value of ℒ(𝑡 2 + 2𝑡 + 3)


2 2 1 2 2 3
a) 𝑠3 + 𝑠2 + 𝑠 b) 𝑠3 + 𝑠2 + 𝑠 c) 0 d) None of these

74) The value of ℒ(𝑠𝑖𝑛2 2𝑡)


8 1
a) 𝑠(𝑠2+16) b) 𝑠(𝑠2 +16) c) 1 d) 0

75) The value of ℒ(𝑒 −𝑎𝑡 )


1 1 1 1
a) 𝑠 b) 𝑠−2𝑎 c) 𝑠+𝑎 d) 𝑠−𝑎

76) The value of ℒ(𝑡 2 𝑒 −3𝑡 )


2 2 2
a) (𝑠+2)3 b) (𝑠+3)2 c) 0 d) (𝑠+3)3

1−𝑒 𝑡
77) The value of ℒ( )
𝑡

𝑠−1 𝑠+1 𝑠+1 𝑠−1


a) b) c) log( ) d) log( )
𝑠 𝑠 𝑠 𝑠

sin 𝑎𝑡
78) The value of ℒ( )
𝑡
𝑠 𝑎 𝑠
a) 𝑎 b) tan−1( 𝑠 ) c) cot −1(𝑎) d) option (a) and (b)

∞ 𝑒 −𝑡 −𝑒 −2𝑡
79) The value of ∫0 𝑑𝑡
𝑡

a) 𝑒 2 b) log 2 c) 1 d) None of these



80) The value of ∫0 𝑡𝑒 −3𝑡 cos 𝑡 𝑑𝑡
1 5 2
a) 25 b) 26 c) 25 d) 0

81) If F(s) is the Laplace transform of f(t) then ℒ −1 {𝐹(𝑠 − 𝑎)} =

a) 𝑒 𝑎𝑡 𝐹(𝑠) b) 𝑒 −𝑎𝑡 𝐹(𝑠) c) 𝑒 𝑎𝑡 𝐹(𝑠/𝑎) d) 𝑒 −𝑎𝑡 𝐹(𝑠/𝑎)


1
82) ℒ −1 (𝑠2+9)
sin 3𝑡 sin 3𝑡
a) sin 3𝑡 b) c) d) cos 3𝑡
3 4

4𝑠−5
83) ℒ −1 {𝑠2−𝑠−2} =

a) 𝑒 2𝑡 + 5𝑒 −𝑡 b) 𝑒 2𝑡 − 5𝑒 −𝑡 c) 𝑒 −2𝑡 + 5𝑒 𝑡 d) 𝑒 −2𝑡 − 5𝑒 −𝑡

84) If ℒ{𝑓(𝑡)} = 𝐹(𝑠) and ℒ{𝑔(𝑡)} = 𝐺(𝑠), then ℒ{𝑓 ∗ 𝑔} =

a) 𝐹(𝑠)𝐺(𝑠) b) 𝐹(𝑠) + 𝐺(𝑠) c) 𝐹(𝑠) − 𝐺(𝑠) d) 𝐹(𝑠)/𝐺(𝑠)


6
85) ℒ −1 (𝑠3 ) =

𝑡3
a) b) 𝑡 3 c) 𝑡 2 d) 𝑡 2 /2
2

86) If ℒ{𝑓(𝑡)} = 𝐹(𝑠), then ℒ −1 {𝐹(𝑎𝑠)} =


1 𝑠 𝑠
a) 𝑎 𝑓(𝑎) b) 𝑓(𝑎) c) f(s) d) f(s)/s
𝑠
87) ℒ −1 {(𝑠2+4)2} =

a) 4𝑡 sin 2𝑡 b) sin 2𝑡 c) t⁡sin 2𝑡 d) sin 4𝑡


𝑠
88) ℒ −1 {(𝑠−2)3 } =

1 1
a) 12 𝑒 2𝑡 𝑡 3 (2 + 𝑡) b) 𝑒 2𝑡 (2 + 𝑡) c) 12 𝑒 2𝑡 (2 + 𝑡) d) None of these
1
89) The value of ℒ −1 {(𝑠+𝑎)2 }

𝑡2
a) 𝑒 −𝑎𝑡 b) 𝑡𝑒 −𝑎𝑡 c) d) None of these
2
𝑠
90) The value of ℒ −1 {𝑠2𝑎2 +𝑏2 }
𝑏𝑡 1 𝑏𝑡
a) cos b) a2 cos c) 1 d) None of these
𝑎 𝑎
𝑠
91) The value of ℒ −1 {(𝑠2+𝑎2)2 }

𝑡 𝑡 𝑡
a) 2𝑎 sin 𝑎𝑡 b) − 2𝑎 sin 𝑎𝑡 c) 2𝑎 cos 𝑎𝑡 d) 1
𝑠
92) The value of ℒ −1 {(𝑠2−1)2}

𝑡 𝑡 𝑡
a) 2 cosh 𝑡 b) 2 sin 𝑡 c) 0 d) 2 sinh 𝑡
1+2𝑠
93) The value of ℒ −1 {(𝑠+2)2(𝑠−1)2}

𝑡 𝑡
a) 3 (𝑒 𝑡 − 𝑒 −2𝑡 ) b) 3 (𝑒 𝑡 + 𝑒 −2𝑡 ) c) (𝑒 𝑡 + 𝑒 −2𝑡 ) d) None of these
1
94) The value of ℒ −1 {(𝑠+1)(𝑠2+2𝑠+2)}

a) 𝑒 𝑡 (1 − cos 𝑡) b) 𝑒 −𝑡 (1 − cos 𝑡) c) 0 d) 𝑒 𝑡 (1 + sin 𝑡)


1
95) The value of ℒ −1 {𝑠(𝑠2 +𝑎2)}

1−cos 𝑎𝑡 1−cos 𝑎𝑡 1+sin 𝑎𝑡


a) b) c) d) 0
𝑎2 𝑎 𝑎

𝑠2
96) The value of ℒ −1 {(𝑠−1)3 }

𝑒𝑡 𝑒𝑡 𝑒𝑡
a) (𝑡 2 + 4𝑡) b) (𝑡 2 − 4𝑡 + 2) c) (𝑡 2 + 4𝑡 + 2) d) None of these
2 2 2
𝑠
97) The value of ℒ −1 {(𝑠+2)2 }

a) 𝑒 2𝑡 b) 𝑒 −2𝑡 (1 − 2𝑡) c) 𝑒 −2𝑡 2𝑡 d) 0


𝑠
98) The value of ℒ −1 {(𝑠2+𝑘 2)}

a) sin 𝑎𝑡 b) sin 𝑝𝑡 c) cos 𝑎𝑡 d) cos 𝑘𝑡

99) If ℒ{𝑓(𝑡)} = 𝐹(𝑠), then ℒ[𝑡𝑓(𝑡)]

a) F(s) b) F’(s) c) 0 d) –F’(s)

100) If ℒ{𝑓(𝑡)} = 𝐹(𝑠), then ℒ{𝑓(𝑎𝑡)}


1 1 1
a) 𝑎 𝐹(𝑠) b) 𝑎 𝐹(𝑎/𝑠) c) 𝑎 𝐹(𝑠/𝑎) d) None of these
ANSWERS:

1)c 2) c 3)a 4)c 5)a 6)c 7)a 8)c 9)c 10)b 11)a 12)a 13)d 14)a 15)c 16)a 17)a
18)a 19)a 20)b 21)c 22)a 23)b 24)a 25)d 26)a 27)a 28)b 29)b 30)b 31)a 32)a 33)d 34)b
35)b 36)a 37)a 38)b 39)b 40)d 41)d 42)d 43)b 44)c 45)a 46)d 47)c 48)b 49)d 50)c 51)b
52)d 53)b 54)d 55)b 56)c 57)b 58)a 59)d 60)b 61)b 62)a 63)a 64)b 65)a 66)a 67)b 68)c
69)c 70)a 71)a 72)a 73)b 74)a 75)c 76)d 77)d 78) d 79)b 80)c 81)a 82)b 83)a 84)a 85)a
86)a 87)a 88)a 89)b 90)b 91)a 92)d 93)a 94)b 95)a 96)c 97)b 98)d 99) d 100) c

You might also like